Peran Strategis Pendidikan dan Kesehatan dalam Pembangunan Ekonomi: Membangun Human Capital untuk Masa Depan - Nermelita Kaloko; Nurhapijah Sihombing; Syahrina Aisyah Lubis; Tukma Putri Romaito Tanjung (PPIMAN Pusat Publikasi Ilmu Manajemen, 2025)
Education and health are two main pillars in human development that are closely related. Both contribute greatly to economic growth, improving the quality of life, labor productivity, and encouraging innovation. This study uses a qualitative method with literature studies from journals, books, and other references related to human capital, education, and economic growth. Education is seen as an essential social service, while health includes physical, mental, and social well-being. Human capital is a crucial component in supporting organizational success and economic development.